Tempered glass

By physically strengthening the glass with an average thermal expansion coefficient of 50 to 350°C and a glass transition temperature of 20×10-7 to 50×10-7/°C and a glass transition temperature of 560°C, the compression stress reduction of heat-resistant glass at high temperatures is solved. The problem of this achieves the effect that surface stress is not easily reduced at high temperatures.

CN115572060BActive Publication Date: 2025-02-07AGC INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202211251919.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-03-28
Filing Date
2018-05-31
Publication Date
2025-02-07
Estimated Expiration
2038-05-31

AI Technical Summary

Technical Problem

When existing physically strengthened heat-resistant glass is used for a long time at high temperatures, the compression stress on the surface is easily reduced, resulting in a decrease in heat resistance.

Method used

The glass with an average thermal expansion coefficient of 50 to 350°C is physically strengthened, and the glass transition temperature is above 560°C to form a reinforcement with excellent heat resistance and high compression stress. Glass.

Benefits of technology

It is achieved that when used for a long time at high temperature, the compression stress on the surface is not easily reduced and excellent heat resistance is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003888387230000151
    Figure BDA0003888387230000151
  • Figure BDA0003888387230000161
    Figure BDA0003888387230000161
  • Figure BDA0003888387230000171
    Figure BDA0003888387230000171
Patent Text Reader

Abstract

The present invention relates to a method for increasing the average thermal expansion coefficient of 50 to 350°C to 20×10 ‑7 ~50×10 ‑7 / ℃, tempered glass obtained by physically strengthening glass with a glass transition temperature of 560℃ or above, and tempered glass obtained by physically strengthening glass containing R2O: 0 to 4% (R2O is specified in the specification) and B2O3: 5 to 25% expressed as molar percentages based on oxides.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention application with application number 201880037353.5, application date May 31, 2018, and invention name “TEMPERED GLASS”. Technical Field

[0002] The present invention relates to a tempered glass which is excellent in heat resistance and in which surface compressive stress is unlikely to decrease even when exposed to high temperature for a long period of time. Background Art

[0003] In the past, heat-resistant glass was used in various applications such as top plates of heaters such as heating cookers, window materials of high-temperature furnaces, and building materials that require fire resistance. For example, low-expansion lithium aluminum silicate crystallized glass was used in the past as the top plate of heaters such as heating cookers. However, low-expansion lithium aluminum silicate crystallized glass has a brownish color tone, which is difficult to match with the surrounding color tones and appearance.

[0004] In order to improve heat resistance, heat-resistant glass is sometimes subjected to physical strengthening such as air cooling strengthening (see Patent Document 1, etc.). For example, general-purpose low-expansion glass, heat-resistant glass obtained by physically strengthening borosilicate glass such as PYREX (a registered trademark of Corning Incorporated) and TEMPAX (a registered trademark of Schott Corporation) can be used, and low-expansion tempered glass "PYRAN" (a registered trademark of Schott Corporation) can be used.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2016-500642. Summary of the invention

[0008] However, conventional physically strengthened heat-resistant glass has a problem in that the surface compressive stress is relaxed when used for a long period of time at high temperatures, and the surface compressive stress is reduced.

[0009] Therefore, an object of the present invention is to provide a tempered glass which has excellent heat resistance and in which the surface compressive stress is unlikely to decrease even when exposed to high temperature for a long period of time.

[0010] The present inventors have conducted intensive studies and, as a result, have found that the above-mentioned problems can be solved by the following tempered glass, thereby completing the present invention.

[0011] That is, the tempered glass according to one embodiment of the present invention has an average thermal expansion coefficient of 20×10 -7 ~50×10 -7 / °C and physically strengthens glass having a glass transition temperature of 560°C or higher.

[0012] The above-mentioned glass may contain, expressed in terms of molar percentage based on oxides:

[0013] R2O: 0-5% (wherein R2O is at least one of Li2O, Na2O and K2O);

[0014] RO: 5-15% (wherein RO is at least one of MgO, CaO, SrO and BaO);

[0015] SiO2: 55-80%; and

[0016] B2O3: 0~25%.

[0017] In addition, a tempered glass according to another embodiment of the present invention is obtained by physically tempering the following glass, wherein the glass contains, expressed in terms of molar percentage based on oxides:

[0018] R2O: 0-4% (wherein R2O is at least one of Li2O, Na2O and K2O); and

[0019] B2O3: 5~25%.

[0020] In the above-mentioned tempered glass, the above-mentioned glass may further contain, expressed in terms of molar percentage based on oxides:

[0021] SiO2: 55-80%; and

[0022] RO: 5-15% (wherein RO is at least one of MgO, CaO, SrO and BaO).

[0023] In addition, the average thermal expansion coefficient of the glass at 50 to 350°C may be 20×10 -7 ~50×10 -7 / ℃.

[0024] In addition, the glass transition temperature of the above-mentioned glass may be 560° C. or higher.

[0025] In addition, the above-mentioned glass may contain Fe2O3 in an amount of 0.0001 to 0.2% expressed as a weight percentage based on oxide.

[0026] Furthermore, the above-mentioned glass may contain at least one selected from chloride, SnO2 and SO3 in an amount of 0.0001 to 2.0% by weight.

[0027] In addition, the above-mentioned glass preferably has a devitrification temperature lower than the viscosity of 10 3 dPa·s temperature.

[0028] In addition, the glass preferably has a viscosity of 10 3 The electrical conductivity σ at a temperature of dPa·s is 2.5 ms / m or more in terms of logσ value.

[0029] In addition, when a 1 mm thick glass having a mirror-finished surface is used as the above-mentioned glass, the load of the Vickers hardness tester indenter at which the crack generation rate when the above-mentioned tempered glass is indented with a Vickers hardness tester indenter becomes 50% is preferably 100 gf or more.

[0030] In the above-mentioned tempered glass, the surface compressive stress is preferably 5 to 200 MPa.

[0031] The thickness of the tempered glass is preferably 2 mm or more.

[0032] In the above-mentioned tempered glass, the stress residual rate after heat treatment at 400° C. for 12 hours is preferably 75% or more.

[0033] In addition, in the above-mentioned tempered glass, the stress residual rate after heat treatment at 400° C. for 21 hours is preferably 60% or more.

[0034] The above-mentioned tempered glass may further include an organic printed layer on one main surface.

[0035] In the above case, the color tone difference ΔE when comparing the tempered glass further including the organic printed layer with the tempered glass having only the organic printed layer is preferably 10 or less.

[0036] The above-mentioned tempered glass may further include a ceramic printed layer on at least a part of one main surface.

[0037] In addition, the present invention also relates to a glass having an average thermal expansion coefficient of 20×10 -7 ~50×10 -7 / ℃,

[0038] The glass transition temperature is above 560°C.

[0039] Thickness: 2~15mm,

[0040] Expressed in terms of molar percentage based on oxides, it contains SiO2: 65-75%, Al2O3: 5-20%, B2O3: 0-25%, MgO: 0.1-10%, CaO: 0.1-10%, ZnO: 0-5%, Li2O: 0.1-2.5%, Na2O: 0-1.5%, ZrO2: 0-2.5%, and,

[0041] Expressed as a weight percentage based on oxides, it contains Fe2O3: 0.0001 to 0.2%.

[0042] Furthermore, the present invention relates to a cooking machine including the tempered glass as a top plate.

[0043] Furthermore, the present invention also relates to a kitchen countertop comprising the above-mentioned heating cooking machine.

[0044] The tempered glass of the present invention has excellent heat resistance, and the compressive stress on the surface is unlikely to decrease even when exposed to high temperature for a long period of time. DETAILED DESCRIPTION

[0045] The present invention is described in detail below, but the present invention is not limited to the following embodiments and can be implemented in any manner without departing from the gist of the present invention. It should be noted that in this specification, "to" means above the lower limit and below the upper limit.

[0046] A tempered glass according to one embodiment of the present invention (hereinafter referred to as the first embodiment) has an average thermal expansion coefficient of 20×10 -7 ~50×10 -7 / °C and is obtained by physically strengthening glass having a glass transition temperature of 560°C or higher.

[0047] In the tempered glass of the first embodiment, the average thermal expansion coefficient (α) of the glass is 20×10 -7 ~50×10 -7 / ℃. α is 20×10 -7 / ℃ or above, compressive stress is likely to be generated on the glass surface due to physical strengthening. α is preferably 24×10 -7 / °C or more, more preferably 27×10 -7 / ℃ or more, more preferably 29×10 -7 / ℃ or more, particularly preferably 30×10 -7 / ℃ or more. On the other hand, α is 50×10 -7 / °C or less, the stress generated when exposed to high temperature is reduced, and cracking due to thermal shock can be suppressed. α is preferably 45×10 -7 / °C or less, more preferably 40×10 -7 / °C or less, more preferably 35×10 -7 / ℃ or less, particularly preferably 32×10 -7 / ℃ below.

[0048] In addition, the average thermal expansion coefficient (α) of glass can be measured using a thermomechanical analyzer (TMA).

[0049] In addition, in the first embodiment of the tempered glass, the glass transition temperature (Tg) of the glass is 560°C or higher. If Tg is 560°C or higher, even when used for a long time at high temperature, the relaxation of the surface compressive stress introduced by physical strengthening is suppressed, and the surface compressive stress is not easily reduced. From this viewpoint, Tg is preferably 590°C or higher, preferably 650°C or higher, more preferably 690°C or higher, further preferably 740°C or higher, particularly preferably 760°C or higher, and most preferably 810°C or higher.

[0050] In addition, the glass transition temperature (Tg) of glass can be measured using a thermomechanical analyzer (TMA).

[0051] On the other hand, Tg is preferably below 900°C. In the case of performing physical strengthening such as air-cooling strengthening on the glass, the glass is heated to a temperature above Tg and then rapidly cooled. Here, if Tg exceeds 900°C, it is necessary to set the heating temperature to a high temperature higher than Tg for physical strengthening. Therefore, when performing physical strengthening, peripheral components such as parts (clamps) that hold the glass are exposed to high temperatures, which may significantly reduce the life of the peripheral components or require expensive components with excellent heat resistance. From this point of view, Tg is more preferably below 820°C. On the other hand, in the case of wanting to implement physical strengthening at low cost, it is further preferably below 770°C, further preferably below 720°C, and particularly preferably below 670°C.

[0052] The tempered glass of the first mode has a compressive stress (compressive stress layer) on the surface. Here, the compressive stress value of the surface is not particularly limited, but from the viewpoint of improving heat resistance, it is preferably 5MPa or more. The compressive stress is more preferably 10MPa or more, more preferably 15MPa or more, and more preferably 20MPa or more. In addition, for example, from the viewpoint of suppressing the scattering of glass and ensuring safety during use even if rupture occurs, the compressive stress on the surface is preferably 200MPa or less. The compressive stress is more preferably 100MPa or less, more preferably 60MPa or less, and more preferably 39MPa or less. Here, the compressive stress on the surface can be measured using a surface stress measuring device or a birefringence measuring device.

[0053] In the first embodiment of the tempered glass, the glass composition is not particularly limited as long as it can obtain a glass composition that satisfies the above requirements. For example, the glass composition of the second embodiment of the tempered glass described later can be applied. It should be noted that in the first embodiment of the tempered glass, the average thermal expansion coefficient of the glass at 50 to 350°C is 20×10 -7 ~50×10 -7 / ℃, as long as the glass transition temperature is 560℃ or higher, it can contain 5% or less R2O.

[0054] In addition, the tempered glass of another embodiment of the present invention (hereinafter referred to as the second embodiment) is a tempered glass obtained by physically strengthening glass containing R2O: 0 to 4% (wherein R2O is at least one of Li2O, Na2O and K2O) and B2O3: 5 to 25% expressed as a molar percentage based on oxides.

[0055] The following describes the composition of the tempered glass of the second embodiment. It should be noted that, unless otherwise specified, the content (%) of each component represents the molar percentage based on the oxide. Among them, the content of Fe2O3 described later is expressed as a weight percentage based on the oxide, and the total content of at least one selected from chloride, SnO2 and SO3 is expressed as a weight percentage.

[0056] R2O is a useful component for promoting the melting of glass raw materials and adjusting the thermal expansion coefficient, viscosity, etc. It is also a useful component for improving the electrical conductivity of glass at high temperatures. Here, R2O represents at least one of Li2O, Na2O and K2O. By making the content of R2O less than 4%, the thermal expansion coefficient of the glass can be reduced, and the stress generated when exposed to high temperatures can be reduced. In addition, even when used for a long time at high temperatures, the relaxation of the surface compressive stress introduced by physical strengthening will be suppressed, and the surface compressive stress will not be easily reduced. The content of R2O is preferably less than 3%, and more preferably less than 2%. In addition, although R2O may not be contained (the content may also be 0%), R2O may also be contained in order to improve the solubility of the glass. At this time, the content of R2O is preferably more than 0.5%, more preferably more than 1%, and more preferably more than 1.5%.

[0057] Li2O is a component useful in promoting the melting of glass raw materials, adjusting the thermal expansion coefficient, viscosity, etc., and increasing the stress residual rate under a state of reduced viscosity. It is also a component useful in improving the electrical conductivity of glass at high temperatures. In order to reduce the thermal expansion coefficient of glass and reduce the stress generated when exposed to high temperatures, it is preferably 4% or less, more preferably 3% or less, further preferably 2.5% or less, and further preferably 2% or less. In addition, although Li2O may not be contained (the content may be 0%), it may be contained in order to suppress the thermal expansion coefficient of the glass and adjust the glass transition temperature. At this time, the content of Li2O is preferably 0.1% or more, more preferably 0.5% or more, further preferably 1% or more, and particularly preferably 1.5% or more.

[0058] Na2O is a component useful in promoting the melting of glass raw materials and adjusting the thermal expansion coefficient, viscosity, etc. It is also a component useful in improving the electrical conductivity of glass at high temperatures. In order to reduce the thermal expansion coefficient of the glass and reduce the stress generated when exposed to high temperatures, it is preferably 3% or less, and more preferably 2% or less. In addition, although Na2O may not be contained (the content may be 0%), it may be contained in order to reduce the viscosity of the glass and improve manufacturability. In this case, the content of Na2O is preferably 0.1% or more, more preferably 0.5% or more, further preferably 1% or more, and particularly preferably 1.5% or more.

[0059] K2O is a component useful for promoting the melting of glass raw materials and adjusting the thermal expansion coefficient, viscosity, etc. It is also a component useful for improving the electrical conductivity of glass at high temperatures. In order to reduce the thermal expansion coefficient of the glass and reduce the stress generated when exposed to high temperatures, it is preferably 2% or less, more preferably 1% or less, further preferably 0.5% or less, and particularly preferably 0.2% or less. In addition, although K2O may not be contained (the content may be 0%), it may be contained in order to reduce the viscosity of the glass and improve manufacturability. In this case, the content of K2O is preferably 0.1% or more, more preferably 0.5% or more, further preferably 1% or more, and particularly preferably 1.5% or more.

[0060] In addition, from the viewpoints of material cost, glass stability, and adhesion with inorganic ink, Li2O / (Na2O+K2O) is preferably 1.0 or less, and more preferably 0.9 or less, and even more preferably 0.85 or less.

[0061] B2O3 is a useful component for adjusting the thermal expansion coefficient of glass, so it can be contained. When B2O3 is contained in order to suppress the thermal expansion coefficient of glass, suppress viscosity or adjust the glass transition temperature, it is preferably 1% or more, more preferably 3% or more, further preferably 5% or more, further preferably 7% or more, and particularly preferably 9% or more, and particularly preferably 11% or more when the viscosity is to be suppressed. On the other hand, in order to improve the weather resistance of glass, the content of B2O3 is 25% or less, preferably 20% or less, more preferably 15% or less, further preferably 10% or less, and further preferably 4.7% or less when a particularly high glass transition temperature is desired.

[0062] SiO2 is the main component of glass. In order to improve the weather resistance of glass and increase the expansion coefficient of glass, the content of SiO2 is preferably 55% or more, more preferably 60% or more, further preferably 65% ​​or more, further preferably 68% or more, and particularly preferably 70% or more. In addition, in order to reduce the viscosity of glass and improve manufacturability, the content of SiO2 is preferably 80% or less, more preferably 75% or less, further preferably 73% or less, and further preferably 71% or less.

[0063] In order to improve the weather resistance of the glass and to increase the glass transition temperature of the glass, Al2O3 may be contained, preferably 4% or more, more preferably 7% or more, further preferably 9% or more, and further preferably 10.5% or more. On the other hand, in order to improve the acid resistance of the glass, the Al2O3 content is preferably 20% or less, more preferably 14% or less, further preferably 12.5% ​​or less, further preferably 11% or less, and particularly preferably 10% or less when it is desired to further improve the manufacturing stability of the glass.

[0064] In order to reduce the viscosity of the glass and improve the manufacturability, RO (here, RO is at least one of MgO, CaO, SrO and BaO) may be contained, preferably 5% or more, more preferably 8% or more, and further preferably 9% or more. In addition, in order to control the expansion coefficient of the glass, reduce the devitrification temperature and improve the productivity, the content of RO is preferably 15% or less, more preferably 12% or less, and further preferably 10% or less.

[0065] In order to control the expansion coefficient and reduce the viscosity of the glass to improve manufacturability, MgO may be contained, and the content of MgO is preferably 1% or more, more preferably 3% or more, and further preferably 5% or more. On the other hand, in order to reduce the expansion coefficient of the glass and lower the devitrification temperature of the glass to improve productivity, the content of MgO is preferably 10% or less, more preferably 8% or less, and further preferably 7% or less.

[0066] In order to control the expansion coefficient and reduce the viscosity of the glass to improve manufacturability, CaO may be contained, and the CaO content is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more. On the other hand, in order to reduce the devitrification temperature of the glass and improve productivity, the CaO content is preferably 10% or less, more preferably 8% or less, further preferably 6% or less, and most preferably 4% or less.

[0067] In order to lower the devitrification temperature of the glass and improve productivity, SrO may be contained, and the content of SrO at this time is preferably 0.5% or more, more preferably 1% or more, and further preferably 2.5% or more. On the other hand, in order to lower the devitrification temperature of the glass and improve productivity, the content of SrO is preferably 7% or less, more preferably 5% or less, and further preferably 3% or less.

[0068] In order to increase the glass transition temperature, lower the devitrification temperature of the glass and improve productivity, BaO may be contained, and the content of BaO is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more. On the other hand, in order to reduce the thermal expansion coefficient of the glass, lower the devitrification temperature of the glass and improve productivity, the content of BaO is preferably 7% or less, more preferably 5% or less, and further preferably 3% or less.

[0069] In order to improve the chemical resistance of the glass, ZrO2 may be contained, and the content of ZrO2 is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more. On the other hand, in order to reduce the devitrification temperature of the glass and improve productivity, the content of ZrO2 is preferably 5% or less, more preferably 4% or less, and further preferably 3% or less.

[0070] In order to reduce the high temperature viscosity of the glass and improve the manufacturability, ZnO may be contained, and the content of ZnO is preferably 0.5% or more, more preferably 1% or more, and most preferably 2.7% or more. On the other hand, in order to reduce the thermal expansion coefficient of the glass and reduce the glass devitrification temperature to improve productivity, the content of ZnO is preferably 10% or less, more preferably 5% or less, and further preferably 3% or less.

[0071] In order to improve the clarity of the glass without damaging the color of the glass and to control the temperature of the bottom substrate of the melting furnace, Fe2O3 may be contained. In this case, the content of Fe2O3 is preferably 0.0001% or more, more preferably 0.001% or more, and further preferably 0.01% or more, expressed as a weight percentage based on an oxide. On the other hand, in order to maintain the color of the glass, the color difference ΔE when comparing the tempered glass further provided with an organic printed layer containing an inorganic filler with the organic printed layer containing only an inorganic filler is adjusted to 10 or less, and the content of Fe2O3 is preferably 0.2% or less, more preferably 0.15% or less, further preferably 0.1% or less, and most preferably 0.05% or less, expressed as a weight percentage based on an oxide.

[0072] P2O5 is an effective component for preventing the crystallization and devitrification of glass and stabilizing the glass, and can be contained. In order to exert the above-mentioned effect well, the content of P2O5 is preferably 1% or more, more preferably 2.5% or more, and further preferably 3.5% or more. On the other hand, by setting the content of P2O5 to 10% or less, the glass can be stabilized without excessively increasing the high-temperature viscosity of the glass. The content of P2O5 is preferably 8% or less, and more preferably 6% or less.

[0073] Typically, the glass of this embodiment is substantially composed of the above-mentioned components, but may contain other components (such as TiO 2 ) up to a total of 2.5 mol % within a range not impairing the purpose of the present invention.

[0074] In addition, as a clarifier for melting glass, SO3, chloride, fluoride, halogen, SnO2, Sb2O3, As2O3, etc. may be appropriately contained. In addition, in order to adjust the color, coloring components such as Ni, Co, Cr, Mn, V, Se, Au, Ag, Cd, etc. may be contained. In addition, when coloring is actively desired, coloring components such as Fe, Ni, Co, Cr, Mn, V, Se, Au, Ag, Cd, etc. may be contained in a range of 0.1% or more.

[0075] It should be noted that when at least one selected from chloride, SnO2 and SO3 among the above-mentioned other components is contained, from the viewpoint of clarity, the total content thereof is preferably 0.0001% or more, more preferably 0.0005% or more, and further preferably 0.001% or more, expressed in weight percentage. On the other hand, in order not to affect the characteristics of the glass, the total content thereof is preferably 2.0% or less, more preferably 1.5% or less, and further preferably 1.0% or less, expressed in weight percentage.

[0076] In addition, the tempered glass of the second aspect preferably has a compressive stress layer having a compressive stress of 5 to 200 MPa on the surface. The technical significance thereof is the same as that of the tempered glass of the first aspect.

[0077] In the tempered glass of the second embodiment, the average thermal expansion coefficient (α) of the glass at 50 to 350° C. is preferably 20×10 -7 ~50×10 -7 / °C. In addition, the tempered glass of the second embodiment preferably has a glass transition temperature (Tg) of 560°C or higher. The technical significances thereof are the same as those of the tempered glass of the first embodiment.

[0078] The glass of the present invention has a viscosity of 10 3The electrical conductivity σ at temperature T3 of dPa·s is preferably 2.5 ms / m or more in terms of logσ value. If the electrical conductivity σ at temperature T3 is 2.5 ms / m or more in terms of logσ value, electric melting can be well applied in the melting process of the glass, and mass production can be carried out with good energy efficiency. The electrical conductivity σ of the glass at temperature T3 is more preferably 2.6 ms / m or more in terms of logσ value, and further preferably 2.8 ms / m or more in terms of logσ value. In addition, the upper limit of the electrical conductivity σ of the glass at temperature T3 is not particularly limited, but is usually 5.0 ms / m or less in terms of logσ value. When the electrical conductivity σ of the glass at temperature T3 is greater than 5.0 ms / m in terms of logσ value, more electricity is required for heating, and energy efficiency deteriorates. It should be noted that the electrical conductivity σ of the glass at temperature T3 can be measured using a four-probe method.

[0079] In addition, from the perspective of stability during glass production, the devitrification temperature (T L ) is preferably less than the viscosity of 10 3 dPa·s temperature T3. At this time, T3-T L It is preferably 50° C. or higher, more preferably 100° C. or higher, and further preferably 150° C. or higher. The devitrification temperature refers to the lowest temperature at which crystals are not generated inside the glass when the glass is kept at a specific temperature for 12 hours.

[0080] In addition, a glass having a mirror-finished surface and a thickness of 1 mm is used as the above-mentioned glass, and the load of the Vickers hardness tester indenter is preferably 100 gf or more, more preferably 200 gf or more, further preferably 400 gf or more, and further preferably 700 gf or more when the crack generation rate when the glass or the tempered glass obtained by physically strengthening the glass is indented with a Vickers hardness tester indenter becomes 50%. If the load is 100 gf or more, the scratch resistance is excellent, so it can be suitably used in various applications where it is desired that it is not easy to be scratched. The method for measuring the crack generation rate is described in detail in the first embodiment column.

[0081] The thickness of the above-mentioned glass is preferably 2 mm or more. When the thickness of the glass is less than 2 mm, the surface compressive stress generated by physical strengthening may increase. The thickness of the glass is more preferably 2.5 mm or more, and further preferably 3 mm or more. On the other hand, the upper limit of the thickness of the glass is not particularly limited, but is usually 15 mm or less, preferably 10 mm or less. It should be noted that the thickness of the glass is actually the same before and after physical strengthening.

[0082] In the present invention, a preferred embodiment of the glass to be subjected to the strengthening treatment (also referred to as the strengthening glass) is one having an average thermal expansion coefficient of 20×10 -7 ~50×10-7 / ℃, a glass transition temperature of above 560℃, a thickness of 2 to 15mm, and containing, in molar percentage based on oxides, SiO2: 65 to 75%, Al2O3: 5 to 20%, B2O3: 0 to 25%, MgO: 0.1 to 10%, CaO: 0.1 to 10%, ZnO: 0 to 5%, Li2O: 0.1 to 2.5%, Na2O: 0 to 1.5%, ZrO2: 0 to 2.5%, and Fe2O3: 0.0001 to 0.2%, expressed in weight percentage based on oxides.

[0083] In addition, regarding the tempered glass of the present invention, the residual stress rate when heat-treated at 400°C for 12 hours is preferably 75% or more, more preferably 80% or more, and further preferably 85% or more. It should be noted that the upper limit of the residual stress rate when heat-treated at 400°C for 12 hours is not particularly limited, and the higher the more preferably, for example, 99.9%. Here, the residual stress rate can be obtained as follows.

[0084] First, a circular plate with a mirror surface is made from the glass before the compressive stress layer is formed. The photoelastic constant is calculated using the circular plate compression method using the prepared circular plate. Next, a flat or circular sample is suspended on a fixture made of a SUS rod using a platinum wire and kept at a temperature 200°C higher than the glass transition temperature for 10 minutes. After heating, the glass is taken out with the fixture and rapidly cooled in the atmosphere. The prepared rapidly cooled glass is cut, and the cut surface is optically polished, and the delay is measured using a birefringence measuring device. Then, the stress generated (surface compressive stress) is obtained by dividing the measured delay value by the above-mentioned photoelastic constant and the glass thickness, which is defined as the "surface compressive stress before relaxation".

[0085] On the other hand, the glass having compressive stress on the surface obtained as described above is subjected to heat treatment at 400°C for 12 hours, taken out into the air, and the retardation of the glass after the heat treatment is measured using a birefringence measuring apparatus. Then, the surface compressive stress after the heat treatment is obtained by dividing the measured retardation value by the photoelastic constant and the glass thickness, and this is defined as "relaxed surface compressive stress".

[0086] Then, the residual stress ratio was calculated based on the following formula.

[0087] Stress residual rate = {(surface compressive stress after relaxation) / (surface compressive stress before relaxation)}×100(%)

[0088] In addition, regarding the tempered glass of the present invention, the residual stress rate when heat-treated at 400°C for 21 hours is preferably 60% or more, more preferably 70% or more, and further preferably 75% or more. It should be noted that the upper limit of the residual stress rate when heat-treated at 400°C for 21 hours is not particularly limited, and the higher the value, the more preferred, but is, for example, 99.9%. It should be noted that the residual stress rate when heat-treated at 400°C for 21 hours can be measured in the same manner as the residual stress rate when heat-treated at 400°C for 12 hours, except that the heat treatment time is changed to 21 hours.

[0089] In addition, regarding the tempered glass of the present invention, the residual stress rate when heat-treated at 500°C for 21 hours is preferably 20% or more, more preferably 30% or more, and further preferably 40% or more. It should be noted that the upper limit of the residual stress rate when heat-treated at 500°C for 21 hours is not particularly limited, and the higher the value, the more preferred, but is, for example, 60%. It should be noted that the residual stress rate when heat-treated at 500°C for 21 hours can be measured in the same manner as the residual stress rate when heat-treated at 400°C for 12 hours, except that the heat treatment temperature is changed to 500°C and the heat treatment time is changed to 21 hours.

[0090] Furthermore, regarding the tempered glass of the present invention, the residual stress rate when heat-treated at 600°C for 21 hours is preferably 0.1% or more, more preferably 1% or more, further preferably 2% or more, and more preferably 3% or more. It should be noted that the upper limit of the residual stress rate when heat-treated at 600°C for 21 hours is not particularly limited, and the higher the value, the more preferred, but is, for example, 50%. It should be noted that the residual stress rate when heat-treated at 600°C for 21 hours can be measured in the same manner as the residual stress rate when heat-treated at 400°C for 12 hours, except that the heat treatment temperature is changed to 600°C and the heat treatment time is changed to 21 hours.

[0091] In addition, regarding the tempered glass of the present invention, when three tempered glasses of 100 mm in length × 100 mm in width × 4 mm in thickness are prepared and only a portion of 10 mm in diameter at the center of one main surface is heated at 400°C for 150 hours and then immediately placed in water at 25°C, it is preferred that all three tempered glasses do not generate in-plane cracks starting from the heated portion (heated portion). It is further preferred that no in-plane cracks are generated after heating at 400°C for 300 hours, and it is most preferred that no in-plane cracks are generated after heating at 400°C for 1000 hours. In the case of such tempered glass, the generation of in-plane cracks due to rapid temperature changes can be appropriately prevented, and thus it can be used safely.

[0092] In the present invention, the temperature at which the glass melts, that is, the temperature at which the viscosity of the glass becomes 10 2The temperature T2 of dPa·s is preferably 1800° C. or lower, more preferably 1750° C. or lower, and further preferably 1700° C. or lower. When the temperature T2 is 1800° C. or lower, the homogeneity of the glass and the productivity become good.

[0093] In the glass of the present invention, the temperature which serves as a criterion for the clarity of the glass, that is, the temperature at which the viscosity of the glass becomes 10 3 The temperature T3 of dPa·s is preferably 1600° C. or lower, more preferably 1550° C. or lower, and further preferably 1500° C. or lower. When the temperature T3 is 1600° C. or lower, the degassing property of the glass becomes good.

[0094] In the present invention, the temperature at which the glass viscosity becomes 10 is a reference example when the glass is formed. 4 The temperature T4 of dPa·s is preferably 1350° C. or lower, more preferably 1300° C. or lower, and further preferably 1250° C. or lower. When the temperature T4 is 1350° C. or lower, the formability of the glass becomes good.

[0095] In addition, the temperature T2, the temperature T3, and the temperature T4 can be measured by using a rotational viscometer.

[0096] The tempered glass of the present invention is not crystallized glass but transparent glass, so, for example, if it is used in the top plate of a heating cooker, in order to conceal the interior of the heating cooker, an organic printed layer obtained from ink containing an inorganic filler can be further provided on the main surface. Typically, the organic printed layer containing an inorganic filler is provided on the main surface (back surface) opposite to the main surface in contact with the heating object in the top plate (tempered glass) of the heating cooker.

[0097] The color tone of the organic printed layer containing the inorganic filler is not particularly limited, but the color tone is preferably matched with the kitchen countertop disposed around the cooking machine because a sense of unity in color tone can be imparted.

[0098] In this case, the color tone difference ΔE when comparing the tempered glass further provided with the organic printed layer containing the inorganic filler and the organic printed layer containing only the inorganic filler is preferably 10 or less, more preferably 7 or less, and most preferably 3.5 or less. The color tone difference ΔE of 10 or less means that the tempered glass is substantially colorless and transparent, and the color tone difference caused by the presence or absence of the tempered glass is sufficiently small, so the color tone of the organic printed layer containing the inorganic filler can be directly applied, and a sense of unity with the surrounding color tone can be easily obtained. Here, the color tone difference ΔE can be measured, for example, in the following manner.

[0099] First, a white reference plate was prepared, and the color tone (L1*, a1*, b1*) was evaluated using the i7 manufactured by X-right. Next, a 4mm thick glass substrate (tempered glass) was placed on the white reference plate, and the color tone (L2*, a2*, b2*) of the white reference plate was evaluated through the glass substrate. These color tone differences can be calculated using the following formula.

[0100] ΔE=((L1*-L2*) 2 +(a1*-a2*) 2 +(b1*-b2*) 2 ) 1 / 2

[0101] In addition, for the purpose of providing various displays or decorations, preventing scratches, etc., the tempered glass of the present invention may further include a ceramic printed layer. For example, when the ceramic printed layer is used in a top plate of a heating cooking machine, it is typically provided on the main surface (surface) on the side that contacts the heating object, that is, the main surface on the side opposite to the side on which the organic printed layer containing the inorganic filler is provided. It should be noted that the ceramic printed layer can be formed continuously, but it can also be formed in various discontinuous forms such as dots. That is, the ceramic printed layer can be provided on the entire main surface of the tempered glass, or it can be provided only on a part.

[0102] The method for producing the tempered glass of the present invention is not particularly limited, and the method for shaping the molten glass is also not particularly limited, and the tempered glass can be produced, for example, in the following manner.

[0103] First, the glass raw materials are appropriately prepared, heated to about 1600-1650°C to melt them, and then homogenized by degassing, stirring, etc., and formed into plates by known float process, down-draw process (melting process, etc.), pressing process, flattening process, etc., or cast into blocks, and then slowly cooled and cut into the desired size to manufacture glass (glass plate). Grinding is performed as needed, but the surface of the glass plate can also be treated with a fluorine agent on the basis of or instead of grinding. If the stable production of glass plates is considered, the float process or the down-draw process is preferred, and if the production of large glass plates is considered, the float process is particularly preferred. In addition, when grinding the glass plate, from the viewpoints of manufacturing stability, product appearance, etc., it is preferred to grind so that the flatness is less than 1.0 mm.

[0104] Next, the obtained glass sheet is heated to a temperature higher than the glass transition temperature Tg, preferably 50 to 200°C higher than Tg, and then rapidly cooled by blowing a cooling medium such as air. Therefore, the vicinity of the surface is rapidly cooled to below the strain point to solidify, and by increasing the difference in expansion with the slower cooling interior, the interior is relatively greatly contracted relative to the vicinity of the surface, thereby imparting compressive stress to the vicinity of the surface. Here, from the viewpoint of the flatness of the product, it is preferred to heat at a temperature 50 to 100°C higher than Tg. It should be noted that the wind pressure of the cooling medium blown onto the glass sheet is not particularly limited, but in order to appropriately and rapidly cool the heated glass sheet, the maximum wind pressure is preferably 2KPa or more.

[0105] In addition, in the tempered glass of the present invention, by performing physical strengthening and heat treatment or chemical strengthening, the stress after stress relaxation can be compensated when the glass is kept at a high temperature. Alternatively, the above-mentioned glass (tempered glass) may be chemically strengthened instead of physically strengthened.

[0106] In addition, assuming that the tempered glass of the present invention is applied to the top plate of a cooking machine, for example, a ceramic printing layer can be formed by performing ceramic printing on the main surface (surface) of the top plate on the side in contact with the heating object. Ceramic printing can be performed, for example, by applying a paste containing inorganic pigment powder, glass powder, etc. to a glass plate and then calcining it. It should be noted that the calcination step can be performed separately from the heating of the glass plate in the physical strengthening treatment, but from the viewpoint of reducing the number of steps, it is preferably performed simultaneously with the heating of the glass plate in the physical strengthening treatment.

[0107] In addition, assuming that the tempered glass of the present invention is used, for example, in the top plate of a cooking machine, an organic printing layer containing an inorganic filler can be formed by performing organic printing containing an inorganic filler on the main surface (back surface) of the top plate opposite to the main surface in contact with the heating object. The organic printing containing an inorganic filler can be performed, for example, by applying various inks to a glass plate and then heating and drying it as needed. It should be noted that the step of performing organic printing can be performed, for example, after the physical strengthening treatment of the glass plate, but is not limited to this.

[0108] The tempered glass of the present invention described above is excellent in heat resistance and has a surface compressive stress that is not easily reduced. Therefore, it can be suitably used in various applications such as the top plate of a heater such as a cooking machine, a window material of a high-temperature furnace, and a building material that requires fire resistance. In addition, the tempered glass of the present invention is not a crystallized glass but a transparent glass, so it also has the advantage of matching the color tone and appearance of the surroundings. It should be noted that a coloring component can be appropriately contained as described above according to the color tone and appearance of the surroundings.

[0109] In addition, the present invention also provides a heating cooker having the above-mentioned tempered glass as a top plate. As a heating cooker, in addition to a heating cooker using an induction heating method (induction heating cooker), it can also be a heating cooker using a gas combustion method (gas heating cooker). In addition, according to the present invention, a kitchen countertop including the heating cooker is also provided. Here, in the kitchen countertop, the above-mentioned tempered glass as the top plate of the heating cooker and the workbench (top plate) of the kitchen countertop can be different, but the top plate of the heating cooker and the workbench (top plate) of the kitchen countertop can also be an integrated object, that is, the above-mentioned tempered glass can have the functions of both the top plate of the heating cooker and the workbench (top plate) of the kitchen countertop.

[0110] Example

[0111] The present invention will be specifically described below with reference to Examples and Comparative Examples, but the present invention is not limited to these.

[0112] The raw materials were prepared according to the compositions listed in Tables 1 to 3, expressed as molar percentages or weight percentages based on oxides, placed in a platinum crucible, and placed in a 1650°C resistance-heated electric furnace for 2 hours for melting, degassing, and homogenization. It should be noted that the compositions listed in Tables 1 to 3 are described by rounding off significant figures, so the total content of each component in the glass composition may not be 100%. In addition, the glass composition containing Cl is a formula composition.

[0113] The obtained glass was cast into a mold, kept at Tg+50°C for 1 hour, and then cooled to room temperature at a rate of 1°C / min to obtain a glass block. Next, the glass block was cut and polished, and both surfaces were mirror-finished to obtain the glass of each example.

[0114] (Average thermal expansion coefficient, glass transition temperature, temperature T2, temperature T3 and temperature T4)

[0115] The average thermal expansion coefficient (α) (unit: °C) of the obtained glass at 50 to 350°C was measured using a thermomechanical analyzer (TMA). -1 ) and glass transition temperature (Tg) (unit: °C). The viscosity of the glass was measured using a rotational viscometer to determine when it became 10 2 dPa·s at temperature T2, the viscosity of the glass becomes 10 3 The temperature T3 of dPa·s and the viscosity of the glass become 10 4 dPa·s temperature T4. The results are shown in Tables 1 to 3. In addition, blank columns and "ND" indicate not measured. In addition, underlined values ​​are calculated values.

[0116]

Table 1

[0117]

[0118]

Table 2

[0119]

[0120]

Table 3

[0121]

[0122] <Experiment 1>

[0123] (Surface compressive stress)

[0124] For each of the glasses of Examples 1 to 2, 4 to 5, and 21 prepared to have a thickness of 5 mm, the surface compressive stress (generated stress) was measured in the following manner.

[0125] First, a circular plate with a mirror surface is made from the glass before the compressive stress layer is formed. The photoelastic constant is obtained by using the circular plate compression method using the prepared circular plate. Next, a flat or circular sample is suspended on a fixture composed of a SUS rod using a platinum wire and kept at a temperature 200°C higher than the glass transition temperature (physical strengthening temperature) for 10 minutes. After heating, the glass is taken out with the fixture and the glass is rapidly cooled in the atmosphere. The prepared rapidly cooled glass is cut, and the cut surface is optically polished, and the delay is measured using a birefringence measuring device. Then, the stress generated (surface compressive stress) is obtained by dividing the measured delay value by the above-mentioned photoelastic constant and the glass thickness, and it is defined as the "surface compressive stress before relaxation".

[0126] Table 4 shows the photoelastic constant (nm / cm / MPa), physical strengthening temperature (unit: °C), retardation before relaxation (unit: nm), and surface compressive stress before relaxation (unit: MPa) of the glass.

[0127] (Stress Residual Rate)

[0128] In addition, the residual stress rate of the obtained glass after heat treatment at 400° C. for 12 hours was measured as follows.

[0129] First, the glass (tempered glass) having a compressive stress layer on the surface obtained as described above is subjected to heat treatment at 400°C for 12 hours, and then taken out into the air, and the retardation of the glass after the heat treatment (hereinafter also referred to as "relaxed retardation") is measured using a birefringence measuring device. Then, the surface compressive stress after the heat treatment is obtained by dividing the measured value of the relaxed retardation by the photoelastic constant and the glass thickness, and this is defined as the "relaxed surface compressive stress".

[0130] Then, the stress residual rate was calculated based on the following formula.

[0131] Stress residual rate = {(surface compressive stress after relaxation) / (surface compressive stress before relaxation)}×100(%)

[0132] Table 4 shows the retardation after relaxation (unit: nm), the surface compressive stress after relaxation (unit: MPa), and the stress residual rate (%).

[0133]

Table 4

[0134] Table 4

[0135]

[0136] The tempered glass of Example 21, which does not satisfy the requirements specified in the present invention, has a low residual stress rate when heat-treated at 400°C for 12 hours or longer. On the other hand, the tempered glasses of Examples 1-2 and 4-5, which satisfy the requirements specified in the present invention, have a high residual stress rate when heat-treated at 400°C for 12 hours or longer, that is, the compressive stress on the surface is not easily reduced even when exposed to high temperature for a long time.

[0137] Experiment 2

[0138] (Surface compressive stress)

[0139] For each of the glasses of Examples 5 to 6, 10 to 12, 21 to 22, 24, and 26 prepared to have a thickness of 4 mm, the surface compressive stress (generated stress) was measured as follows.

[0140] First, a circular plate with a mirror surface is made from the glass before the compressive stress layer is formed. The photoelastic constant is calculated using the circular plate compression method using the prepared circular plate. Next, a flat or circular plate-shaped sample is suspended on a fixture made of a SUS rod using a platinum wire and kept at 730°C for 10 minutes. After heating, the glass is taken out with the fixture, and compressed air is blown into the atmosphere to quickly cool the glass. The prepared rapidly cooled glass is cut, and the cut surface is optically polished, and the delay is measured using a birefringence measuring device. Then, the stress generated (surface compressive stress) is obtained by dividing the measured delay value by the above-mentioned photoelastic constant and the glass thickness, which is defined as the "surface compressive stress before relaxation".

[0141] Table 5 shows the photoelastic constant (nm / cm / MPa) of the glass, the heat treatment temperature (unit: °C), the delay before relaxation (unit: nm), and the surface compressive stress before relaxation (unit: MPa). It should be noted that the photoelastic constant (nm / cm / MPa) of the glass of Examples 6, 10, and 11 is a calculated value.

[0142] (Stress Residual Rate)

[0143] In addition, the obtained glass was heat-treated at 400° C. for 21 hours, 150 hours, or 300 hours, and the residual stress rate was measured as follows.

[0144] First, the glass (tempered glass) having a compressive stress layer on the surface obtained as described above is subjected to heat treatment at 400°C for a predetermined time (21 hours, 150 hours or 300 hours), and then taken out into the air, and the retardation of the glass after the heat treatment (hereinafter also referred to as "relaxed retardation") is measured using a birefringence measuring device. Then, the surface compressive stress after the heat treatment is obtained by dividing the measured value of the relaxed retardation by the photoelastic constant and the glass thickness, and this is defined as the "relaxed surface compressive stress".

[0145] Then, the stress residual rate was calculated based on the following formula.

[0146] Stress residual rate = {(surface compressive stress after relaxation) / (surface compressive stress before relaxation)}×100(%)

[0147] Table 5 shows the surface compressive stress (unit: MPa) and the stress residual rate (%) after relaxation.

[0148]

Table 5

[0149] Table 5

[0150]

[0151] The tempered glass of Example 21, which does not satisfy the requirements specified in the present invention, has a low residual stress rate when heat-treated at 400°C for 21 hours or longer. On the other hand, the tempered glasses of Examples 5 to 6, 10 to 12, 22, 24, and 26, which satisfy the requirements specified in the present invention, have a high residual stress rate when heat-treated at 400°C for 12 hours or longer, that is, the compressive stress on the surface is not easily reduced even when exposed to high temperature for a long time.

[0152] Experiment 3

[0153] (Surface compressive stress)

[0154] For each of the glasses of Examples 12, 22 to 24, and 26 prepared to have a thickness of 4 mm, the surface compressive stress (generated stress) was measured as follows.

[0155] First, a circular plate with a mirror surface is made from the glass before the compressive stress layer is formed. The photoelastic constant is calculated using the circular plate compression method using the prepared circular plate. Next, a flat or circular sample is suspended on a fixture made of a SUS rod using a platinum wire and kept at 825°C for 10 minutes. After heating, the glass is taken out with the fixture, and compressed air is blown to the glass in the atmosphere for rapid cooling. After cutting the rapidly cooled glass, the cut surface is optically polished, and the delay is measured using a birefringence measuring device. Then, the measured delay value is divided by the above-mentioned photoelastic constant and the glass thickness to calculate the stress (surface compressive stress), which is defined as the "surface compressive stress before relaxation".

[0156] Table 6 shows the photoelastic constant (nm / cm / MPa) of the glass, the heat treatment temperature (unit: °C), the retardation before relaxation (unit: nm), and the surface compressive stress before relaxation (unit: MPa).

[0157] (Stress Residual Rate)

[0158] In addition, the obtained glass was heat-treated at 600° C. for 21 hours or 150 hours, and the residual stress rate was measured as follows.

[0159] First, the glass (tempered glass) having a compressive stress layer on the surface obtained as described above is subjected to heat treatment at 600°C for a predetermined time (21 hours or 150 hours), and then taken out into the air, and the retardation of the glass after the heat treatment (hereinafter also referred to as "relaxed retardation") is measured using a birefringence measuring device. Then, the surface compressive stress after the heat treatment is obtained by dividing the measured value of the relaxed retardation by the photoelastic constant and the glass thickness, and this is defined as the "relaxed surface compressive stress".

[0160] Then, the stress residual rate was calculated based on the following formula.

[0161] Stress residual rate = {(surface compressive stress after relaxation) / (surface compressive stress before relaxation)}×100(%)

[0162] Table 6 shows the surface compressive stress (unit: MPa) and the stress residual rate (%) after relaxation.

[0163]

Table 6

[0164] Table 6

[0165]

[0166] From the above results, it was confirmed that, in any of the tempered glasses of Examples 12, 22 to 24, and Example 26, stress of 0.7% or more remained even when the tempered glasses were kept at 600° C. for 21 hours.

[0167] <Experiment 4>

[0168] (Surface compressive stress)

[0169] For each of the glasses of Examples 13, 29, and 30 produced to have a thickness of 4 mm, the surface compressive stress (generated stress) was measured as follows.

[0170] First, a circular plate with a mirror surface is made from the glass before the compressive stress layer is formed. The photoelastic constant is calculated using the circular plate compression method using the prepared circular plate. Next, the flat or circular plate-shaped sample is kept in a molten salt containing 99wt% KNO3 and 1wt% NaNO3 at 450-500°C for 6 hours. After washing with water, the cut surface is optically polished and the delay is measured using a birefringence measuring device. Then, the stress generated (compressive stress on the surface) is calculated by dividing the measured delay value by the above-mentioned photoelastic constant and the glass thickness, and it is defined as the "surface compressive stress before relaxation".

[0171] Table 7 shows the photoelastic constant (nm / cm / MPa) of the glass, the heat treatment temperature (unit: °C), the retardation before relaxation (unit: nm), and the surface compressive stress before relaxation (unit: MPa).

[0172] (Stress Residual Rate)

[0173] In addition, the obtained glass was heat-treated at 500° C. for 2 hours or 150 hours, and the stress residual rate was measured as follows.

[0174] First, the glass (tempered glass) having a compressive stress layer on the surface obtained as described above is subjected to heat treatment at 500°C for a predetermined time (2 hours or 150 hours), and then taken out into the air, and the retardation of the glass after the heat treatment (hereinafter also referred to as "relaxed retardation") is measured using a birefringence measuring device. Then, the surface compressive stress after the heat treatment is obtained by dividing the measured value of the relaxed retardation by the photoelastic constant and the glass thickness, and this is defined as the "relaxed surface compressive stress".

[0175] Then, the stress residual rate was calculated based on the following formula.

[0176] Stress residual rate = {(surface compressive stress after relaxation) / (surface compressive stress before relaxation)}×100(%)

[0177] Table 7 shows the surface compressive stress (unit: MPa) and the stress residual rate (%) after relaxation.

[0178]

Table 7

[0179] Table 7

[0180] <Experiment 5>

[0181] (Surface compressive stress)

[0182] The compressive stress (generated stress) on the surface of the glass of Example 13 produced to have a thickness of 4 mm was measured as follows.

[0183] First, a circular plate with a mirror surface is made from the glass before the compressive stress layer is formed. The photoelastic constant is calculated using the circular plate compression method using the prepared circular plate. Next, a flat or circular plate-shaped sample is suspended on a fixture made of a SUS rod using a platinum wire and kept at 750°C for 10 minutes. After heating, the glass is taken out with the fixture, and compressed air is blown to the glass in the atmosphere and rapidly cooled. The prepared rapidly cooled glass is kept in a molten salt containing 99wt% KNO3 and 1wt% NaNO3 at 500°C for 6 hours. After washing with water, the cut surface is optically polished, and the delay is measured using a birefringence measuring device. Then, the stress generated (surface compressive stress) is calculated by dividing the measured delay value by the above-mentioned photoelastic constant and the glass thickness, and it is defined as the "surface compressive stress before relaxation".

[0184] Table 8 shows the photoelastic constant (nm / cm / MPa) of the glass, the heat treatment temperature (unit: °C), the retardation before relaxation (unit: nm), and the surface compressive stress before relaxation (unit: MPa).

[0185] (Stress Residual Rate)

[0186] In addition, the obtained glass was heat-treated at 500° C. for 2 hours or 150 hours, and the residual stress rate was measured as follows.

[0187] First, the glass (tempered glass) having a compressive stress layer on the surface obtained as described above is subjected to heat treatment at 500°C for a predetermined time (2 hours or 150 hours), and then taken out into the air, and the retardation of the glass after the heat treatment (hereinafter also referred to as "relaxed retardation") is measured using a birefringence measuring device. Then, the surface compressive stress after the heat treatment is obtained by dividing the measured value of the relaxed retardation by the photoelastic constant and the glass thickness, and this is defined as the "relaxed surface compressive stress".

[0188] Then, the stress residual rate was calculated based on the following formula.

[0189] Stress residual rate = {(surface compressive stress after relaxation) / (surface compressive stress before relaxation)}×100(%)

[0190] Table 8 shows the surface compressive stress (unit: MPa) and the stress residual rate (%) after relaxation.

[0191]

Table 8

[0192] Table 8

[0193]

[0194] (Presence or absence of devitrification at temperature T3)

[0195] The glasses of Examples 2, 5, 10 to 15, 17, 19 to 20, and 23 to 31 were examined for the presence or absence of devitrification at the temperature T3. As a result, none of the glasses had devitrification.

[0196] (Conductivity σ at temperature T3)

[0197] The viscosity of the glasses of Examples 2, 5, 12, 17, 20 to 22, 24, 26, 29 and 30 was measured by the four-probe method to be 10 3 The electrical conductivity σ at the temperature T3 is expressed in dPa·s. The measurement results are shown in Table 9 as logσ (ms / m) values.

[0198]

Table 9

[0199] Table 9

[0200]

[0201] (50% crack initiation load)

[0202] The glasses of Examples 5, 12, 17 to 24 and 26 having a mirror-finished surface and a thickness of 1 mm were used, and the Vickers hardness tester was used with a pyramid-shaped diamond indenter having an edge angle of 110°, and the crack generation rate P when a load of 100 gf was applied was measured. That is, in an atmospheric atmosphere, under the conditions of a temperature of 24°C and a dew point of 35 to 45°C, the load of the Vickers hardness tester was set to 50 gf, 100 gf, 200 gf, 300 gf, 500 gf, and 1000 gf, and the Vickers hardness tester indenter was punched into 10 points under each load, and the number of cracks generated at the four corners of the indentation was measured. The value obtained by dividing the number of cracks generated by the number of cracks that can be generated, 40, was taken as the crack generation rate P. In addition, the load at which the crack generation rate becomes 50% was obtained by regression calculation, and this value was taken as the 50% crack generation load.

[0203] In addition, the 50% crack initiation load was measured in the same manner for the glass of Example 12 which was physically strengthened at a physical strengthening temperature of 750°C.

[0204] These measurement results are shown in Table 10.

[0205]

Table 10

[0206] Table 10

[0207]

[0208] A white reference plate was prepared, and the color tone (L1*, a1*, b1*) was evaluated using i7 manufactured by X-right. Next, a glass of Example 12 with a thickness of 4 mm was placed on the white reference plate, and the color tone (L2*, a2*, b2*) of the white reference plate was evaluated through the glass. The color tone difference was calculated using the following formula.

[0209] ΔE=((L1*-L2*) 2 +(a1*-a2*) 2 +(b1*-b2*) 2 ) 1 / 2

[0210] In addition, the color tone difference was measured in the same manner for crystallized glass (Neoceram, manufactured by Nippon Electric Glass Co., Ltd., "Ref" in Table 9).

[0211] These results are shown in Table 11.

[0212]

Table 11

[0213] Table 11

[0214]

[0215] Although the present invention is described in detail with reference to specific embodiments, various changes and modifications can be implemented by those skilled in the art without departing from the purpose and scope of the present invention. This application is based on Japanese patent application (Special Application 2017-111183) filed on June 5, 2017 and Japanese patent application (Special Application 2018-062142) filed on March 28, 2018, and its contents are hereby cited as a reference.

Claims

1. A glass with an average thermal expansion coefficient of 20×10 at 50 to 350°C -7 ~38.0×10 -7 / ℃, The glass transition temperature is above 560°C. Thickness: 2~15mm, Expressed in molar percentage based on oxides, it contains SiO2: 65-75%, Al2O3: 5-20%, B2O3: 10-25%, MgO: 0.1-10%, CaO: 0.1-4.5%, ZnO: 0-5%, Li2O: 0.1-0.9%, Na2O: 0-1.5%, ZrO2: 0-2.5%, Li2O / (Na2O+K2O) is less than 1.

0.

2. The glass according to claim 1, wherein: The glass transition temperature is 624°C or higher.

3. The glass according to claim 1 or 2, characterized in that: Expressed as a weight percentage based on oxides, the glass contains 0.0001 to 0.2% Fe2O3.

4. The glass according to claim 1 or 2, wherein: Expressed as weight percentage, the glass contains 0.0001 to 2.0% of at least one selected from chloride, SnO2 and SO3.

5. The glass according to claim 1 or 2, wherein: The devitrification temperature of the glass is lower than the viscosity becomes 10 3 dPa·s temperature.

6. The glass according to claim 1 or 2, wherein: The glass becomes 10 3 The electrical conductivity σ at a temperature of dPa·s is 2.5 ms / m or more in terms of logσ value.

7. The glass according to claim 1 or 2, characterized in that: A glass having a mirror-finished surface and a thickness of 1 mm is used as the glass. When the glass is indented with a Vickers hardness tester indenter, the load of the Vickers hardness tester indenter at which the crack generation rate becomes 50% is 100 gf or more.

8. The glass according to claim 1 or 2, wherein: The surface compressive stress is 5 to 200 MPa.

9. The glass according to claim 1 or 2, wherein: The stress residual rate after heat treatment at 400°C for 12 hours is 75% or more.

10. The glass according to claim 1 or 2, wherein: The residual stress ratio after heat treatment at 400°C for 21 hours was 60% or more.

11. The glass according to claim 1 or 2, wherein: An organic printed layer containing an inorganic filler is further provided on one main surface of the glass.

12. The glass according to claim 11, wherein: When the glass further including the organic printed layer containing the inorganic filler is compared with the glass including only the organic printed layer containing the inorganic filler, the color difference ΔE is 10 or less.

13. The glass according to claim 1 or 2, wherein: A ceramic printed layer is further provided on at least a portion of one main surface of the glass. 14 . A cooking machine comprising the glass according to claim 1 as a top plate.

Citation Information

Patent Citations

  • glass plate for induction cooker

    JP2016500642A

  • Hand tremor correction device

    JP2017111183A

  • Laminate and aqueous coating agent

    JP2018062142A

  • Glass substrate for display and display

    CN101255008A

  • Glass substrate for flat panel displays and method for manufacturing same

    CN103429547A